2005
DOI: 10.1002/mrd.20349
|View full text |Cite
|
Sign up to set email alerts
|

Changes in expression of anti-apoptotic protein, cflip, in granulosa cells during follicular atresia in porcine ovaries

Abstract: Follicular selection is performed in mammalian ovaries, as most follicles undergo atresia during follicular development and growth. Follicular regression is indicated to begin with granulosa cell apoptosis. To reveal the molecular mechanisms of the selection, we examined the changes in the levels of cellular-Flice like inhibitory protein (cFLIP) expression in porcine granulosa cells. cFLIP is the homologue of intracellular apoptosis inducer (procaspase-8/Flice), and has two alternative splicing isoforms: cFLIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 28 publications
3
47
1
1
Order By: Relevance
“…Overexpression of pFADD and pprocaspase-8 induced cell death in the HeLa-K cells. To date, we have investigated the follicular atretic mechanisms of follicular atresia in porcine ovaries [18][19][20][21][22][26][27][28][29][30][31] and have shown that g r a n u l o s a c e l l a p o p t o s i s i s a d o m i n a n t phenomenon in follicular atresia. Therefore, we examined whether overexpressed pFADD and pprocaspase-8 can induce apoptosis in the granulosa cells of human, murine, and porcine origin (KGN, KK1 and JC410, respectively).…”
Section: Apoptosis Inductivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of pFADD and pprocaspase-8 induced cell death in the HeLa-K cells. To date, we have investigated the follicular atretic mechanisms of follicular atresia in porcine ovaries [18][19][20][21][22][26][27][28][29][30][31] and have shown that g r a n u l o s a c e l l a p o p t o s i s i s a d o m i n a n t phenomenon in follicular atresia. Therefore, we examined whether overexpressed pFADD and pprocaspase-8 can induce apoptosis in the granulosa cells of human, murine, and porcine origin (KGN, KK1 and JC410, respectively).…”
Section: Apoptosis Inductivitymentioning
confidence: 99%
“…We previously reported that death ligand/ receptor systems act as initiators of apoptosis in porcine granulosa cells [22,30,31] and showed that an intracellular inhibitory protein, cFLIP, inhibits apoptosis in granulosa cells by binding with the D E D o f F A D D a n d / o r p r o c a s p a s e -8 a n d interrupting the recruitment of procaspase-8 to FADD [29,30]. In the present study, we showed that both the molecular construction and function of apoptotic signaling factors are highly conserved.…”
Section: Apoptosis Inductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical analyses demonstrated that the cFLIP protein is highly expressed in the granulosa cells of healthy follicles but weakly expressed in those of the atretic follicles (Matsuda-Minehata et al, 2005). Luteal tissue formation is characterized by the differentiation and proliferation of cells derived from granulosa, theca, and vascular endothelium in the post-ovulatory follicle (Jablonka-Shariff et al, 1993;Murphy, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The researches in this subject showed that granulosa cells of healthy follicles had highly expressed cFLIP L mRNA and proteins, whereas the atretic ones had decreased levels (Goto et al, 2004). The mRNA levels of cFLIP S in granulosa cells are low and showed no changes among the stages of follicular development (Matsuda-Minehata et al, 2005. cFLIP acts as a survival promoting factor in granulosa cells and not only inhibits Fas-signalling, but also can inhibit TNF α and TRAIL signalling (Manabe et al, 2008;Cheng et al, 2007;Manabe et al, 2003).…”
Section: Antiapoptotic Regulators In the Cellmentioning
confidence: 95%